Methyl 3-(4-methoxybenzoyl)propionate - Ali, Sajid (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(12)H(14)O(3), contains two independent molecules, in which the benzene rings are oriented at a dihedral angle of 72.08 (3)°. In the crystal structure, intermolecular C—H⋯O hydrogen bonds link the molecules into centrosymmetric dimers. There are also C—H⋯π contacts between aromatic CH groups and the benzene rings.